Perioperative Anesthesia Challenges in a Neonate with Concurrent Intussusception and Abdominal Compartment Syndrome: A Rare Clinical Scenario - Pratama Nanda; Dino Irawan; Aditya Permana (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Intussusception and abdominal compartment syndrome (ACS) are severe surgical emergencies in pediatric populations, particularly in neonates. The concurrent presentation of both conditions is exceptionally rare and presents formidable perioperative anesthetic challenges. Case presentation: We report the case of a 2-month-old male neonate weighing 6.9 kg who presented with a 4-day history of bloody stools and bilious vomiting following blunt abdominal trauma inflicted by a 12 kg sibling. Clinical examination and imaging confirmed concurrent intussusception with abdominal compartment syndrome. The patient presented with significant hematologic derangements including severe leukopenia (WBC 1,180/μL), anemia (hemoglobin 9.2 g/dL), thrombocytosis, coagulopathy (INR 1.88), and electrolyte abnormalities. Emergency rapid sequence induction anesthesia was employed with careful fluid management utilizing the Holliday-Segar formula to prevent exacerbation of compartment pressures. A successful exploratory laparotomy with resection of necrotic small bowel segments was performed. Conclusion: The case demonstrates the critical importance of comprehensive preoperative assessment, meticulous fluid management strategies, and multidisciplinary collaboration in managing complex neonatal surgical emergencies. This rare clinical scenario highlights unique anesthetic considerations and provides valuable insights into perioperative management of ACS in the neonatal population.